AA-RM WRESTLING: COMPARING ANALOGICAL APPROACHES AND RULE MODELS FOR LEGAL REASONING. (September 2021) - Rigoni, Adam
ABSTRACT: Legal reasoning is commonly thought of as being based on either rules or analogies. More specifically, there is ongoing debate regarding whether precedential reasoning is best characterized as rule-based or analogical. This article continues that work by comparing recent and representative approaches from each camp, namely, Stevens's analogical model and the "rule-based" model of Horty and Rigoni. In the course of the comparison improvements on each approach are suggested and the improved models serve as the basis for the ultimate evaluation. The evaluation demonstrates that the "best" approach depends on the goals one has in theorizing legal reasoning as well as the jurisprudential assumptions one is willing to make.